MEF2A Regulates the MEG3-DIO3 miRNA Mega Cluster-Targeted PP2A Signaling in Bovine Skeletal Myoblast Differentiation - Wang, Yaning (Int J Mol Sci, 2019)
Understanding the molecular mechanisms of skeletal myoblast differentiation is essential for studying muscle developmental biology. In our previous study, we reported that knockdown of myocyte enhancer factor 2A (MEF2A) inhibited myoblast differentiation. Here in this study, we further identified that MEF2A controlled this process through regulating the maternally expressed 3 (MEG3)—iodothyronine deiodinase 3 (DIO3) miRNA mega cluster and protein phosphatase 2A (PP2A) signaling. MEF2A was sufficient to induce MEG3 expression in bovine skeletal myoblasts. A subset of miRNAs in the MEG3-DIO3 miRNA cluster was predicted to target PP2A subunit genes. Consistent with these observations, MEF2A regulated PP2A signaling through its subunit gene protein phosphatase 2 regulatory subunit B, gamma (PPP2R2C) during bovine myoblast differentiation. MiR-758 and miR-543 in the MEG3-DIO3 miRNA cluster were down-regulated in MEF2A-depleted myocytes. Expression of miR-758 and miR-543 promoted myoblast differentiation and repressed PPP2R2C expression. Luciferase activity assay showed that PPP2R2C was post-transcriptionally targeted by miR-758 and miR-543. Taken together, these results reveal that the MEG3-DIO3 miRNAs function at downstream of MEF2A to modulate PP2A signaling in bovine myoblast differentiation.